Comparative efficacy and safety of Faricimab with other intravitreal anti-vascular endothelial growth factor in the treatment of Neovascular age related macular degeneration- A Systematic review and meta-analysis. - Renuga Devi Kaliaperumal; Nandhini P; Reena Mohan; Nallamuthu P; Jenifer Florence Mary J (Asian Journal of Medical Sciences, 2025)
Age-related macular degeneration (AMD) is the leading cause of visual impairment in patients age 50 and older, with an estimated 200 million people affected worldwide. The neovascular subtype of AMD (nAMD) has been associated with worse vision outcomes. At present, intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy is the standard treatment modality for nAMD. Faricimab (Immunoglobulin G1-derived bispecific antibody) is a newer anti-VEGF directed against VEGF-A and angiopoietin-2 used for the treatment of Neovascular AMD. This systematic review was to evaluate the efficacy and safety of Faricimab and compare it with other intravitreal anti-VEGF in the treatment of neovascular AMD. PubMed and Google Scholar were systematically searched until October 2024. The meta-analysis included all published randomized controlled trials that investigated the efficacy and safety of Faricimab over other intravitreal anti-VEGF agents in adults >50 years with neovascular nAMD. Data extraction was guided by a predetermined checklist. Using RevMan 5 software, mean visual, anatomical, and functional outcomes were pooled from the selected studies. The fixed-effect model was used to assess and compare the effectiveness of Faricimab with other intravitreal anti-VEGF therapy. Data analyses were performed in November 2024. The primary outcome was the assessment of the safety and efficacy of Faricimab in the treatment of nAMD. The secondary outcome was to compare the Faricimab (intervention) group with other intravitreal anti-VEGF (control) groups. The initial search yielded 57 records of which 48 articles underwent full-text evaluation, which identified six articles and a total of 4454 patients (intervention group-2226 and control group 2228) were included in the study. The findings were in favor of Faricimab with respect to best corrected visual acuity (BCVA), central subfield thickness (CST), and choroidal neovascularization (CNV) when compared to other intravitreal anti-VEGF. The pooled MD for BCVA between Faricimab and Aflibercept or Ranibizumab was 0.20 (95% CI: 0.14–0.26). In the case of CST, it was −0.16 (95%CI–0.10–0.22) and CNV it was 0.26 (95% CI: 0.32–0.20) Heterogeneity was found in all outcomes and was statistically significant with the P<0.00001. This systematic review and meta-analysis demonstrated that Faricimab showed a comparable efficacy and safety outcome benefits with a reduction in the frequency of injections compared with other intravitreal anti-VEGF drugs, representing a valuable treatment option for nAMD.